Prechemotherapy nursing assessment among adult cancer patients in a university cancer center in Shanghai, China: a best practice implementation project. Issue 3 (30th September 2020) - Wang, Liying; McArthur, Alexa; Lu, Zhenqi; Yang, Yang; Lu, Haiyan; Chen, Fengzhen; Xue, Mei
ABSTRACT: Objective: The current implementation project aimed to promote evidence-based practice with prechemotherapy nursing assessment among adult cancer patients in a large university cancer center in Shanghai, China, over a 6-month timeframe. Introduction: Prechemotherapy nursing assessment is an essential element of cancer patient care, aiming to prevent or minimize potential problems from chemotherapy treatment. Regular comprehensive prechemotherapy assessment is not part of routine care currently in many clinical settings within China. Methods: The project utilized the JBI approach to implementation, incorporating audit and feedback tools. Twelve evidence-based audit criteria were developed for use in the program. A baseline audit was conducted of prechemotherapy nursing assessment among adult cancer patients, with a sample size of 68 patients and 36 nursing staff. Following implementation of systematic strategies based on the analysis of three main barriers, a follow-up audit involving a similar sample as the first audit was conducted using the same audit criteria. Results: The baseline audit indicated that for nursing assessment among adult cancer patients undergoing chemotherapy, the criteria (1, 10, 11 and 12) which related to nurse education, weight measurement, premedication and access device assessment had very high compliance (from 93 to 100%). Compliance for criteria (2, 6, 7, 9) related to medical history, previous exposure to chemotherapy, patients' or caregivers' comprehension of treatment and psychosocial assessment was 0%, while compliance with the other five criteria (3, 4, 5, 8) was low, ranging from 16 to 61%. There was improvement in all 12 criteria in the follow-up audit. Criteria 1, 11 and 12 maintained high compliance (100%). Criterion 2 (patients' medical history), criterion 3 (presence or absence of allergies), criterion 7 (previous exposure to chemotherapy) and criterion 9 (psychosocial elements) demonstrated a significant improvement in compliance. Although progress has been made, there were still some criteria that require further improvement. These included assessment of patients' current diagnosis and cancer status (criterion 4, from 61 to 66%), recent laboratory results (criterion 5, from 31 to 62%), patients' and/or caregivers' comprehension of information regarding the disease and treatment (criterion 6, from 0 to 34%), any previous exposure to chemotherapy agents (criterion 7, from 0 to 57%), and physical assessment of the patient (criterion 8, from 46 to 72%). Conclusion: The project achieved increased compliance with evidence-based best practice in all assessed audit criteria improving the practice of prechemotherapy assessment. Involvement of informatics technology is a great strategy to help overcome barriers, simplify the change process and assist in sustaining evidence-based practice change. Future plans and ideas are in place and have been discussed. Further audits will need to be carried out to improve the validity and quality of nursing assessment.